(untitled) (المجلة الدولية للبحوث العلمية, 2025)
The purpose of this study is to identify the challenges that King Faisal University’s Applied College students have when learning English writing skills and the strategies they employ to overcome these challenges. Because the instructor will be better informed about the issues students have when writing English essays or paragraphs, the study is important. When teaching writing in class, the English language instructor will concentrate more on the issues and errors that students make. Additionally, the English language instructor will develop new approaches to teaching writing skills and provide extra writing tasks to the students. This research holds significance for curriculum designers as well, since it helps them create a detailed plan outlining the requirements for students.